The Practise of Brand Management on Small Culinary Enterprises, An Explorative Study Using In-Dept Interview - Handari, Astrid; Iskandar, Budi Permadi (Journal of Business and Management, 2012)
Brand has been a part of almost every company, especially a big one that exists nowadays. It is a statement, an image, a message, which packed and delivered to the customer, so that they know what the company stands for. Nowadays, intense competition of a small business requires each business to be able to